Young people's transitions into creative work navigating challenges and opportunities - Sefton-Green, Julian; Watkins, S. Craig; Kirshner, Benjamin (Routledge research in education, 2020)
"Exploring how formal and informal education initiatives and training systems in the US, UK and Australia seek to achieve a socially diverse workforce, this insightful book offers a series of detailed case studies to reveal the initiative and ingenuity shown by today's young people as they navigate entry into creative fields of work. Young People's Transitions into Creative Work acknowledges the new and diverse challenges faced by today's youth as they look to enter employment. Chapters trace the rise of indie work, aspirational labour, economic precarity, and the disruptive effects of digital technologies, to illustrate the oinventive ways in which youth from varied socio-economic and cultural backgrounds enter into work in film, games production, music, and the visual arts. From hip-hop to new media arts, the text explores how opportunities for creative work have multiplied in recent years as digital technologies open new markets, new scenes, and new opportunities for entrepreneurs and innovation. This book will be of great interest to researchers, academics and postgraduate students in the fields of youth studies, careers guidance, media studies, vocational education and sociology of education"--